The brown anole dewlap revisited: do predation pressure, sexual selection, and species recognition shape among-population signal diversity? - Baeckens,Simon; Driessens,Tess; Van Damme,Raoul (PeerJ, 2018)
Animal signalling structures are amongst the most variable characteristics, as they are subjected to a diversity of selection pressures. A well-known example of a diverse signalling system in the animal kingdom is the dewlap of Anolis lizards. Dewlap characteristics can vary remarkably among and within species, and also between sexes. Although a considerable amount of studies have attempted to disentangle the functional significance of the staggering dewlap diversity in Anolis, the underlying evolutionary processes remain elusive. In this study, we focus on the contribution of biotic selective pressures in shaping geographic variation in dewlap design (size, colour, and pattern) and dewlap display behaviour at the intraspecific level. Notably, we have tried to replicate and extend previously reported results hereof in both sexes of the brown anole lizard (Anolis sagrei). To do this, we assembled a dataset consisting of 17 A. sagrei heterogeneous island populations from the Caribbean and specifically tested whether predation pressure, sexual selection, or species recognition could explain interpopulational variation in an array of dewlap characteristics. Our findings show that in neither males nor females estimates of predation pressure (island size, tail break frequency, model attack rate, presence of predatory Leiocephalus lizards) or sexual selection (sexual size dimorphism) could explain variation in dewlap design. We did find that A. sagrei males from larger islands showed higher dewlap display intensities than males from smaller islands, but the direct connection with predation pressure remains ambiguous and demands further investigation. Last, we could show indirect support for species recognition only in males, as they are more likely to have a ‘spotted’ dewlap pattern when co-occurring with a higher number of syntopic Anolis species. In conclusion, we found overall limited support for the idea that the extensive interpopulational variability in dewlap design and use in A. sagrei is mediated by variation in their biotic environment. We propose a variety of conceptual and methodological explanations for this unexpected finding.
Keywords: Anolis sagrei; Caribbean islands; Clay models; Dewlap diversity; Display behaviour; Lizards; Predation pressure; Visual signalling system